Impact of Role Ambiguity on Job Satisfaction of Software Product Managers in Nepal - Ojha, Gaurav (Aadim Journal of Multidisciplinary Research, 2025)
Role ambiguity is a multidimensional construct with diverse manifestations that negatively influences the job satisfaction of software product managers in Nepal. This study examines the relationship between different manifestations of role-based ambiguities and their subsequent impact on levels of job satisfaction for software product managers in Nepal. This study has applied a cross-sectional survey research design together with descriptive statistics and multiple-regression analysis to analyze and evaluate the relationships between task-based, responsibility-based, procedural, and authority-based role ambiguities and their negative effects on job satisfaction. This study finds that among different dimensions of role ambiguities, procedural and task-based role ambiguities significantly and negatively affect the job satisfaction of software product managers. Besides, negative effects of both types of task-based and procedural-based ambiguity underline critical areas for organizational interventions. This study has an originality value, as it is the first of its kind of research that examined the impact of different dimensions of role ambiguities on job satisfaction of software product managers recognizing their job design, specifications, and specializations.